The Focal easy guide to Final Cut Pro 5 : for new users and professionals - Young, Rick, 1967- (Focal easy guide series., 2006)
Software packages are complex. Shouldn't software books make it easier? Simplify your life with The Focal Easy Guide to Final Cut Pro 5! This short, full-color book lives up to its name by paring down the software to its essentials. It covers only the key features and essential workflow to get you up and running in no time. When time is of the essence, less is more. With this book you can start cutting immediately, whatever you edit, whatever the format. This is an ideal introduction whether you are a professional moving over to Final Cut Pro from another package.